The structural face of competition, cooperation and coopetition inside business networks - Klimas, Patrycja (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2015)
The structural view on networking as well as the application of the social network analysis in the area of inter-organizational network theory have become more and more popular recently. However, little attention in the previous literature has been paid to the quantitative and structural exploration of networking processes which occur inside i.e. collaboration, competition and coopetition. Drawing on a resource based view and social network analysis, the article presents the usefulness of structural analysis for networking improvement. This research contributes to the network theory by presenting the possible ways of using structural measurements for networking strategy adoption and by applying structural measurements to the seldom explored area of coopetition processes inside networks. Furthermore, some managerial implications as well as some limitations of the presented methods are shown at the end of the paper
Argumenta Oeconomica, 2015, Nr 1 (34), s. 127-155
Keywords: structural analysis; networking; social network analysis; cooperation; collaboration; coopetition; competition